The Integration of Robotics in Surgery: Advancements, Challenges, and Future Prospects - Pushpan, Dr. Parag; S P , Dr. Chinmaya (South Eastern European Journal of Public Health, 2024)
The integration of robotics in surgery marks a transformative advancement in modern medicine, offering unprecedented precision, control, and minimally invasive options. This paper explores the evolution of robotic-assisted surgical systems, from early prototypes to sophisticated platforms like the da Vinci Surgical System, which have redefined operative procedures across multiple specialties. By analyzing key advancements, including enhanced visualization, precise articulation, and AI-assisted decision-making, this study highlights how robotics improves surgical outcomes, reduces recovery times, and minimizes complications. Despite these benefits, the adoption of surgical robotics faces challenges, including high costs, steep learning curves for surgeons, and regulatory hurdles. Additionally, the ethical implications of robotic autonomy in critical medical procedures prompt ongoing debate. This paper also examines the future prospects of robotics in surgery, such as AI-driven diagnostics, remote surgeries, and potential full automation. Through a comprehensive review, this study seeks to provide a nuanced understanding of the impact of robotics on surgical practice and healthcare outcomes, offering insights into both the potential and limitations of robotic integration in surgery.